Philo-physical model for the theory of everything - Ali, Ali Nasser Mohammed (Journal of Humanities & Social Sciences, 2019)
Abstract: Ancient Egyptians and other ancient civilizations relied on a theory that binds all the components of the universe to each other. Because this approach is different from the rules of modern science, we find it difficult to explain how they founded their civilization in such a wonderful way. I have put a conception for the principles of this theory and it was able to explain all phemenona in the universe, materialistic and theological.(*) It depends on an Idea that the whole universe consists of four primary units, of which pairs are formed and the proportion of units in each pair determines their relation to each other and their relation to them in accordance with the principles of this theory It is simple in its totality to the extent that the non-specialist can understand the most complex interpretations of phenomena in simple way it remove the puzzles between philosophy and physics. It is the missing link between the oddity of quantum mechanics and classical physics. This theory will lead us to conceptualize the universe with a new perspective: that the universe is connected to all its components, so Any change at any point in the universe will change the rest of its components. This Theory can explain Phenomenon by different way; such as space-time, the origin of the universe and the interpretation of ambiguity in ancient civilizations.